Analisis Puisi “Jarak 1” Karya Heri Isnaini Dengan Menggunakan Pendekatan Mimetik - Fitriana Fitriana (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2023)
Poetry is beautiful language based on the results of someone's thoughts and feelings expressed in written language. Poetry is an imaginative literary work that contains analogies of meaning with other uses so that the meaning contained in the poem is hidden behind words, similes and aesthetics that not everyone understands the meaning of the poetry conveyed. When reading poetry, it is necessary to read poetry repeatedly to understand the meaning of the poem because the language in poetry has a broad, implied meaning and is difficult to interpret. Therefore, readers must understand how to study poetry with knowledge in order to understand the meaning of the poetry conveyed. The poem by Heri Isnaini with the title "1 Distance" is formed in simple language but is interesting to study. This attracts a reader to study the poem and use it as research material. The aim of this research. The aim of this research is to analyze the meaning in the poem entitled "Distance 1" by Heri Isnaini and convey the content of the poem in detail so that readers can understand the meaning conveyed through this research. This research is also useful for readers to further develop literary works in the form of poetry. The method used in this research uses a qualitative descriptive method which examines the content of the meaning of the poem "1 Distance". In this way, this research will reveal the implied meaning of the poetry presented by the poet. Apart from that, the author dissects this poem using a mimetic approach. Mimetics is an approach in literary criticism regarding imitation or fiction of real life.